Train man : the novel - Nakano, Hitori; Elliott, Bonnie (New York : Del Rey, 2006)
Boy - bashful and not overly brave - defends girl from obnoxious drunk on a Tokyo train. Girl sends boy a thank-you pair of pricey Hermes teacups. Boy's a geek and doesn't know what to do next. End of story for most nerds - but this one turns to the world's largest online message board and asks for help, so for him it's just the beginning. This matchless love story is told through a series of Internet chat room threads. As Train Man, our hero charts his progress and unveils each new crisis - from making conversation to deciding what to wear on a date and beyond - in return, he receives advice, encouragement, warnings, and sympathy from the anonymous netizens. And Train Man discovers the secret to what makes the world go round-and proves we really do live in a universe where anything can happen. --Cover.
Originally published in London by Constable & Robinson, 2006.
"The Internet-generation love story from Japan"--Cover.
Translated from the Japanese.
Keywords: Geeks (Computer enthusiasts) -- Fiction; Love stories